Case studies and analysis of soft clay consolidation accelerated by vertical drains - Yu, Ning. (2013)
Prefabricated vertical drains (PVDs) have been widely used for the improvement of marine clays. As the soft marine clay is highly compressible, it will result in excessive settlement if there is no proper ground improvement. To assess the suitability of the land prior to construction, the degree of consolidation with respect to ultimate settlement can be predicted via i) observational methods through monitoring of settlement plates and piezometer ii) theoretical calculation based on Terzaghi one-dimensional theory iii) numerical technique based on the PVD properties and soil parameters. This study aims to highlight the effectiveness in using numerical technique to predict the settlement through various case studies, and discusses on the factors that may affect the accuracy of prediction.